ANALYSIS OF THE ATTITUDES OF LITHUANIAN ACADEMIC YOUTH TOWARDS ENVIRONMENTALLY RESPONSIBLE BEHAVIOUR WHEN TRAVELLING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the article, the authors analyse the attitudes of Lithuanian academic youth towards environmentally responsible behaviour when travelling. The purpose of the article is to analyse the attitudes of Lithuanian academic youth towards environmentally responsible behaviour when travelling. The research was carried out by means of a quantitative survey (questionnaire). Data collection methods - analysis of scientific literature and sources and questionnaire survey. The article analyses the attitudes of Lithuanian academic youth towards environmentally responsible behaviour when travelling and presents the results of the research conducted. It is concluded that all respondents have heard more or less about the principles of environmentally responsible travel. Most respondents, depending on the situation or the purpose of the trip, try to choose environmentally friendly and sustainable means of transport, and apply various sustainable actions when traveling: avoid plastic, try to support local businesses and culture, etc. When staying in accommodation facilities, respondents also try to behave responsibly and sustainably: save water and electricity, use room heating and cooling services sustainably, etc. Most respondents positively evaluate environmentally responsible behavior when traveling, but even half of the respondents are not ready to pay more for a sustainable trip. In summary, young people’s attitudes towards travel and its impact on environmental responsibility are dynamic and constantly changing. These trends show that young people are ready to seek sustainable solutions and take responsibility for their actions to protect the planet for future generations.